Front Cover: ZNF582 hypermethylation promotes metastasis of nasopharyngeal carcinoma by regulating the transcription of adhesion molecules Nectin‐3 and NRXN3. Issue 12 (16th December 2020) - Zhao, Yin; Hong, Xiao‐Hong; Li, Kang; Li, Ying‐Qing; Li, Ying‐Qin; He, Shi‐Wei; Zhang, Pan‐Pan; Li, Jun‐Yan; Li, Qian; Liang, Ye‐Lin; Chen, Yang; Ma, Jun; et al.
Abstract : The cover image is based on the Original Article ZNF582 hypermethylation promotes metastasis of nasopharyngeal carcinoma by regulating the transcription of adhesion molecules Nectin‐3 and NRXN3 by Yin Zhao et al., https://doi.org/10.1002/cac2.12104 .